Efpeglenatide and Clinical Outcomes With and Without Concomitant Sodium-Glucose Cotransporter-2 Inhibition Use in Type 2 Diabetes: Exploratory Analysis of the AMPLITUDE-O Trial. Issue 8 (14th November 2021) - Lam, Carolyn S.P.; Ramasundarahettige, Chinthanie; Branch, Kelley R.H.; Sattar, Naveed; Rosenstock, Julio; Pratley, Richard; Del Prato, Stefano; Lopes, Renato D.; Niemoeller, Elisabeth; Khurmi, Nardev S.; Baek, Seungjae; Gerstein, Hertzel C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Both sodium-glucose cotransporter-2 (SGLT2) inhibitors and glucagon-like peptide-1 receptor agonists reduce cardiovascular events among patients with type 2 diabetes. However, no cardiovascular outcome trial has evaluated the long-term effects of their combined use. The AMPLITUDE-O trial (Effect of Efpeglenatide on Cardiovascular Outcomes) reported that once-weekly injections of the glucagon-like peptide-1 receptor agonists efpeglenatide (versus placebo) reduced major adverse cardiovascular events (MACEs); MACEs, coronary revascularization, or unstable angina hospitalization (expanded MACEs); a renal composite outcome; and MACEs or death in people with type 2 diabetes and cardiovascular or renal disease. The trial uniquely stratified randomization by baseline or anticipated use of SGLT2 inhibitors and included the highest prevalence at baseline (N=618, 15.2%) of SGLT2 inhibitor use among glucagon-like peptide-1 receptor agonist cardiovascular outcome trials to date. Its results were analyzed to estimate the combined effect of SGLT2 inhibitors and efpeglenatide on clinical outcomes. Methods: Cardiovascular and renal outcomes were analyzed with Cox proportional hazards models adjusted for region, SGLT2 inhibitor randomization strata, and the SGLT2 inhibitor–by–treatment interaction. Continuous variables were analyzed with a mixed-effects models for repeated measures that also included an interaction term. Results: The effect (hazard ratio [95% CI]) of efpeglenatide versus placebo in the absence and presence of baseline SGLT2 inhibitors on MACEs (0.74 [0.58–0.94] and 0.70 [0.37–1.30], respectively), expanded MACEs (0.77 [0.62–0.96] and 0.87 [0.51–1.48]), renal composite (0.70 [0.59–0.83] and 0.52 [0.33–0.83]), and MACEs or death (0.74 [0.59–0.93] and 0.65 [0.36–1.19]) did not differ by baseline SGLT2 inhibitor use ( P for all interactions >0.2). The reduction of blood pressure, body weight, low-density lipoprotein cholesterol, and urinary albumin-to-creatinine ratio by efpeglenatide also appeared to be independent of concurrent SGLT2 inhibitor use (all interaction P ≥0.08). Last, adverse events did not differ by baseline SGLT2 inhibitor use. Conclusions: The efficacy and safety of efpeglenatide appear to be independent of concurrent SGLT2 inhibitor use. These data support combined SGLT2 inhibitor and glucagon-like peptide-1 receptor agonist therapy in type 2 diabetes. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03496298.